Analisis Respon Pertumbuhan Ekonomi Indonesia Akibat External Shock Amerika Serikat dan China - Alvin Sugeng Prasetyo; Mochamad Devis Susandika (UPT Penerbitan Universitas Jember, 2021)
The purpose of this study is to examine and analyze the response to Indonesia's economic growth caused by external shocks from the United States and China. The method used is VECM, because it is stationary at I (1) and there is cointegration. The estimation results show that the uncertainty of China's economic policies and the contribution of China's economic growth has a greater effect than the United States on Indonesia's economic growth. The shock of the rupiah exchange rate against the US dollar was better than the rupiah exchange rate against the RMB. The shock of changes in oil prices was responded negatively by changes in Indonesia's economic growth. In the long term, there are no signs of a movement in response to changes in Indonesia's economic growth towards equilibrium (convergence).